Ethical frameworks for complex medical decision making in older patients: A narrative review. (September 2020) - van Bruchem-Visser, Rozemarijn Lidewij; van Dijk, Gert; de Beaufort, Inez; Mattace-Raso, Francesco
Highlights: Ethical frameworks are meant to assist healthcare professionals. Most frameworks are step-by-step frameworks. They should contain a step-by-step plan, moral values and an approach to balancing. Abstract: Background: With an ageing population physicians are more and more faced with complex medical and moral situations. Medical professional guidelines are often of limited use in these cases. To assist the decision making process, several ethical frameworks have been proposed. Ethical frameworks are analytical tools that are designed to assist physicians and other involved healthcare workers in complex moral decision-making situations. Most frameworks are step-by-step plans that can be followed chronologically during moral case deliberations. Some of these step-by-step plans provide specific moral guidance as to what would constitute a morally acceptable conclusion, while others do not. Objective: In this narrative review we will present and discuss the ethical frameworks used for medically complex situations in older people that have been proposed in literature. Methods: Three electronic databases (embase.com. Medline Ovid and PsychINFO Ovid) were searched from inception to January 24, 2020, with the help of expert librarians. Results: Twenty-three studies were included in the review, containing seventeen different frameworks. Twenty studies described step-by-step-frameworks, with the number of steps varying from three to twelve. In four studies suggestions were made as how to balance conflicting moral values. Conclusions and implications of key findings: Ethical frameworks are meant to assist healthcare professionals who are faced with morally complex decisions in older patients. In our view, these frameworks should contain a step-by-step plan, moral values and an approach to balancing moral values.